ESG disclosure, governance, political connection, and tax Aggressiveness: what information is critical, and is more information always forceful? - Priandhita Sukowidyanti Asmoro; Suresh Ramakrishnan; Sifa Arsyanda; Nurlita Sukma Alfandia; Devi Nur Cahaya Ningsih; Dewi Noor Fatikhah Rokhimakhumullah; Kadarisman Hidayat (Cogent Business & Management, 2024)
This research examines the complex relationships among ESG (Environmental, Social, and Governance) disclosure, corporate governance, political affiliations, and tax aggressiveness (TAG) in basic materials and energy sector companies listed on the Indonesia and Malaysian Stock Exchanges. By focusing on expanding specific information essential to ESG disclosure, as outlined in the GRI Standards, the study aims to evaluate its effectiveness in mitigating TAG. Employing a quantitative approach, the research addresses gaps in previous studies by using Hierarchical Regression to systematically evaluate the incremental impact of each predictor on TAG, offering deeper insights beyond the general effects captured by linear regression. The study’s findings indicate that no combination of variables is universally effective in mitigating TAG across Indonesian and Malaysian corporations. Furthermore, the research highlights the nuanced nature of information disclosure, demonstrating that not all disclosed information is equally significant in curbing TAG. While not confirming legitimacy theory, the study identifies the GRI 2018 and GRI 2019 standards as containing crucial information for Indonesian companies to mitigate tax TAG. A key contribution lies in pinpointing tax‑related disclosures within the GRI 2019 framework as critical influencers, advancing the understanding of how ESG practices impact tax aggressiveness.